2015
DOI: 10.1242/jcs.171496
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of ROS and RNS detection in hematopoietic stem cells − potential issues with probes and target cell population

Abstract: Many studies have provided evidence for the crucial role of the reactive oxygen species (ROS) and reactive nitrogen species (RNS) in the regulation of differentiation and/or self-renewal, and the balance between quiescence and proliferation of hematopoietic stem cells (HSCs). Several metabolic regulators have been implicated in the maintenance of HSC redox homeostasis; however, the mechanisms that are regulated by ROS and RNS, as well as their downstream signaling are still elusive. This is partially owing to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 121 publications
0
9
0
Order By: Relevance
“…The possible response may be in a mtROS-driven mechanism, which has been suggested as a critical regulator of stem cell fate. These reports assume the physiological mtROS concentration in the micro-environmental low O 2 as being crucial for the maintenance of stemness while the enhancement of mtROS over this niche-relevant level leads to the commitment and differentiation [52][53][54][55]. In fact, this physiological mtROS level corresponds to the "steady state" in situ mtROS levels as ones found at physiologically relevant O 2 concentrations [22,35,38].…”
Section: Discussionmentioning
confidence: 97%
“…The possible response may be in a mtROS-driven mechanism, which has been suggested as a critical regulator of stem cell fate. These reports assume the physiological mtROS concentration in the micro-environmental low O 2 as being crucial for the maintenance of stemness while the enhancement of mtROS over this niche-relevant level leads to the commitment and differentiation [52][53][54][55]. In fact, this physiological mtROS level corresponds to the "steady state" in situ mtROS levels as ones found at physiologically relevant O 2 concentrations [22,35,38].…”
Section: Discussionmentioning
confidence: 97%
“…Separate previous studies indicate that NADPH oxidases Nox4 or Nox2 or that mitochondria is the major source of ROS that serve as signaling molecules to promote switching from a quiescent to an angiogenic phenotype in ECs (1,11,13,18,44,50,56,58,62 this question, we applied several methods to measure intracellular redox status due to limitation of each ROS measurement (15,24,30,59 to promote mtROS production via pSer36-p66Shc, thereby enhancing VEGFR2 activation and angiogenic responses. This may represent a novel positive feed-forward ROS-induced ROS release mechanism orchestrated by the Nox4/Nox2/pS36-p66Shc/mtROS axis, which promotes sustained activation of VEGFR2 angiogenesis signaling program (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…To further measure the ROS level in live RGPs during mouse cortical development, we collected the VZ tissues at E11.5, E13.5, E15.5 and E17.5, and prepared neurospheres in culture. We stained the neurospheres with CellROX Green, a cell-permeant dye that measures ROS levels and oxidative stress in live cells (Vlaski-Lafarge and Ivanovic, 2015), and found that ROS levels and oxidative stress progressively increased in the neurospheres prepared at different developmental stages (Fig. S1).…”
Section: Progressive Increase In Oxidative Stress In the Developing Mmentioning
confidence: 99%